The Bergen 4-Day OCD Treatment Delivered in a Group Setting: 12-Month Follow-Up - Hansen, Bjarne; Hagen, Kristen; Öst, Lars-Göran; Solem, Stian; Kvale, Gerd (Frontiers in Psychology, 2018)
The Bergen 4-day concentrated exposure treatment (cET) for obsessive-compulsive disorder (OCD) has proven highly acceptable; with practically no drop-out and a six month remission rate of nearly 70%. The aim of the present study was to evaluate long term gains of the approach, and to compare the results to findings from our recent meta-analysis. Sixty-nine of 95 patients consecutively referred to an outpatient clinic in the specialist health care, were offered the Bergen 4-day treatment. Among the 65 who initiated treatment, 60.0% were classified with “severe” to “extreme” OCD. None of the patients dropped-out during treatment. Independent Yale-Brown Obsessive-Compulsive Scale interviews were conducted post-treatment, and at 3- and 12-month follow-up. Using the international consensus criteria, 83.1% responded to treatment at 12-month follow-up, and 67.7% of patients were classified as recovered. Significant changes were also seen in depression, as measured by Patient Health Questionnaire-9, and in generalized anxiety, as measured by Generalized Anxiety Disorder-7 scale. A total of 89% of the patients rated the treatment as very good and 100% would recommend the treatment to a friend. Compared to results in a recent meta-analysis, the Bergen 4-day treatment is favorable in respect to attrition, response and 12-month recovery. In sum the Bergen 4-day treatment is a feasible way to deliver treatment for OCD, and and the effects are stable at 12-month follow-up. Implications for dissemination are discussed. Keywords: OCD; ERP; concentrated exposure treatment, Bergen 4-day program; group format; long term follow-up; patients' acceptance